I Symposium of Elite Performance in Combat Sports (Revista de Artes Marciales Asiáticas, 2017)
This report presents a summary of the I Symposium of Elite Performance in Combat Sports held in Madrid, May 27, 2017. The symposium, organized by the Faculty of Sport Sciences-INEF of the Polytechnic University of Madrid, aimed to bring science closer to practice. A panel of highly successful athletes involved in karate, fencing, and taekwondo shared their experiences. The speakers presented crucial topics for an optimal preparation and high level performance such as strength training, sport psychology, brain maturation, sports nutrition, competition planning, sport injuries, and perceptual-decision making training.